Developing Technology-Enabled Solutions for College Students to Cope with Factors Leading to Health Problems. Issue 1 (September 2020) - Ishak, Timaf; Torres, Angelica; Asan, Onur
The purpose of this paper is to identify the leading causes of mental health issues among college students and determine a possible solution to mitigate these problems. The data presented was gathered through interviews and analyzed using thematic analysis. The study concluded that college students typically use various technologies to alleviate their stress.